Complicaciones con el uso de la sutura mecánica en cirugía colorrectal - Rodríguez, Gustavo; Bruno, Gerardo; Ruso, Luis; Gatti, Adriana; Quiró, Fernando; Balboa, Oscar (Cirugía del Uruguay, 1998)
The great development of mechanica/ suture and its qualitative impact in colorectal surgery has not been able to avoid persistent mortality due to suture failure which is sti/1 about 5% and rectal stenosis, which is significantly higher than with manual sutures.